Math, asked by khushimjainmvm, 2 months ago

15. Factorize by splitting the middle term: 3m² + 9m + 6​

Answers

Answered by akeertana503
2

\huge\color{blue}{\mid{\fbox{\tt{Question}}\mid}}

  • 3m² + 9m + 6

 \\  \\

\huge\color{cyan}{\mid{\fbox{\tt{Solution}}\mid}}

______________________________________

3m {}^{2}  + 9m + 6 \\  \\ 3m {}^{2}  + 3m + 6m + 6 \\  \\ 3m(m + 1) + 6(m + 1) \\  \\= (m + 1) \: (3m + 6)

______________________________________

Answered by sujatha201089
0

Answer:

3( m+1) ( m+2)

Step-by-step explanation:

3m²+9m+6

= 3m2+3m+6m+6

=3m( u+1) 6( u+1)

=(3m+6) (u+1)

= 3(m+1) (m+2)

Similar questions